Preparation and Evaluation of Polymeric Nanofibers Containing Griseofulvin –Microemulsion by Electrospinning Process: Polymeric Nanofibers Loaded with Microemulsion: Preparation and Evaluation - Shariat Razavi, Fatemeh; Salimi, Anayatollah (Iranian Journal of Pharmaceutical Sciences, 2023)
In this study, the purpose of preparing CS/PVA nanofibers loaded GRF microemulsion is to increase the solubility of Low soluble drug griseofulvin by using microemulsion nanocarrier, and nanofiber was used as a technique for a new product. This drug is one of the antifungal drugs, and its uses are for skin diseases. Therefore, a topical route can be a good option. Chitosan /polyvinyl alcohol (CS/PVA) nanofiber containing griseofulvin (GRF) loaded microemulsion was obtained. The microemulsion comprised oleic acid and Transcutol P as the oil phase, Span20 and Labrasol as the surfactant, and Plurol oleique as the cosurfactant. Formulations were prepared with a ME(GRF): polymer ratio (30: 70) and (40: 60) and a polymeric solution containing chitosan (2%) and polyvinyl alcohol (10%) at two weight ratio (20: 80) and (10: 90), respectively. The physicochemical characteristics of the GRF-CS/PVA nanofibers were evaluated. The differential scanning calorimetry (DSC) study showed the amorphous state of the GRF-loaded microemulsions and PVA polymer embedded into the nanofibers. The entrapment efficiency percentage of GRF in the mats was approximately 66.67% - 88.89%. Drug release behavior showed controlled and slow release of drugs that are affected by the type of microemulsion formulation and the ratio of polymers used in nanofibers.